1999
DOI: 10.1200/jco.1999.17.10.3173
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in Metastatic Transitional-Cell Carcinoma and Prognostic Factors Predicting Outcome of Therapy

Abstract: The presence of baseline KPS less than 80% or visceral metastasis has an impact on survival. Reporting the proportion of patients with zero, one, and two risk factors will facilitate understanding of the relevance of the median survival in phase II trials. Phase III trials should stratify patients according to the number of risk factors to avoid imbalance in treatment arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
364
3
12

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(402 citation statements)
references
References 19 publications
23
364
3
12
Order By: Relevance
“…methotrexate þ vinblastine, or doxorubicin þ cisplatin) is approximately 8 months (Sternberg et al, 1989). It is known that pretreatment prognostic features have an impact on individual patient outcome, thus the variation in reported survival in patients treated with chemotherapy may be biased by these features (Bajorin et al, 1999;Calabro and Sternberg, 2002).…”
mentioning
confidence: 99%
“…methotrexate þ vinblastine, or doxorubicin þ cisplatin) is approximately 8 months (Sternberg et al, 1989). It is known that pretreatment prognostic features have an impact on individual patient outcome, thus the variation in reported survival in patients treated with chemotherapy may be biased by these features (Bajorin et al, 1999;Calabro and Sternberg, 2002).…”
mentioning
confidence: 99%
“…Currently, Karnofsky Performance scores and presence of visceral metastases are reported to correlate with outcome of treatment. 18 Given the molecular knowledge of urothelial tumorigenesis and chemosensitivity, more precise methods for predicting response to anticancer therapy seem possible.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that 63% of the patients enrolled had received their initial chemotherapy in either the neoadjuvant or adjuvant settings. 16 Response rates in Phase II trials of patients with advanced bladder carcinoma can be influenced significantly by patient selection, as described by Bajorin et al 14 Their study concentrated on prognostic factors associated with response and identified performance status and the sites of metastatic disease as major response parameters. In the salvage setting, other factors in addition to those described the Bajorin et al 14 will likely influence response rates, including the time to disease progression, the drugs initially received by the patients, and the setting of initial chemotherapy (i.e., adjuvant/neoadjuvant versus therapy for metastatic disease).…”
Section: Discussionmentioning
confidence: 99%
“…16 Response rates in Phase II trials of patients with advanced bladder carcinoma can be influenced significantly by patient selection, as described by Bajorin et al 14 Their study concentrated on prognostic factors associated with response and identified performance status and the sites of metastatic disease as major response parameters. In the salvage setting, other factors in addition to those described the Bajorin et al 14 will likely influence response rates, including the time to disease progression, the drugs initially received by the patients, and the setting of initial chemotherapy (i.e., adjuvant/neoadjuvant versus therapy for metastatic disease). As is the case for many solid tumors, the therapeutic goals of salvage therapy need further characterization (i.e., palliation versus survival prolongation), given the limited impact of chemotherapy on survival in the initial treatment of patients with advanced urothelial carcinoma reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation